Policy Communication In Protecting Women And Children: A Study Of Local Regulation Implementation By PPKBP3A Kepahiang District In Preventing Sexual Violence - Ade Irawati; Sugeng Suharto; Gushevinalti (STAI Bumi Silampari, 2026)
This article examines the communication dimensions of public policy implementation in the context of women and children's protection against sexual violence in Kepahiang District, Bengkulu Province, Indonesia. Using Local Regulation No. 10 of 2016 on Protection of Women and Children from Acts of Violence as the normative basis, this study analyzes how the Office of Population Control, Family Planning, Women's Empowerment and Child Protection (PPKBP3A) communicates prevention programs to the public, coordinates with stakeholders, and conveys policy messages to potential beneficiaries and the community at large. Drawing on Mazmanian and Sabatier's (1983) policy implementation framework and feminist communication theory, the study employs a qualitative-descriptive approach with in-depth interviews, participatory observation, and document analysis. Findings reveal that while institutional frameworks exist, critical communication gaps persist: gender-biased messaging, victim-blaming cultural narratives, and weak inter-agency information flows significantly reduce the effectiveness of prevention campaigns. The study further documents that in Bengkulu Province, 207 sexual violence cases involving children were recorded in 2024 by the Ministry of Women's Empowerment and Child Protection (KemenPPA), with Kepahiang District reporting 15 cases in early 2025. These figures point to a systemic failure where policy communication fails to disrupt patriarchal social structures that normalize violence. The article recommends a gender-responsive communication strategy, stronger coordination networks, and community-based messaging frameworks to enhance policy effectiveness.